Virgil & Owen - Bogan, Paulette (Bloomsbury, 2015)
Virgil the penguin finds a polar bear and tries to claim it as his own, but the polar bear wants to splash with the terns, slide with the seals, twirl with all the penguins, and be called by his name--Owen.